Pimikralimus in the Treatment of Adopic Dermatitis - Salamova Lola Abdurahimovna (Zien Journals, 2022)
Data on the mechanisms of formation and methods of effective treatment of atopic dermatitis (AD) are presented. The main directions of pathogenetically substantiated treatment of AD, differentiated correction of concomitant pathology are described in detail. The external therapy of atopic skin lesions in children with the use of modern dermatological cosmetics is presented in particular detail.
Keywords: Atopic dermatitis; treatment; pimecrolimus